Pengaruh Inventory Turn Over, Returm on Assets dan Debt to Assets Ratio Terhadap Tax Avoidance pada Perusahaan Manufaktur di BEI Tahun 2013-2017 - Misral Misral; Sri Rahmayanti; Desi Anita Sari (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
This study aims to determine: (1) the effect of inventory turn over on tax avoidance on manufacturing companies on the Indonesia Stock Exchange; (2) the effect of return on assets on tax avoidance on manufacturing companies on the Indonesia Stock Exchange; (3) the effect of debt to assets ratio on tax avoidance on manufacturing companies on the Indonesia Stock Exchange.The population used is manufacturing companies that have been and are still listed on the Indonesia Stock Exchange in 2013-2017. The determination of the sample in this study used a purposive sampling method, until 66 company samples were obtained from a population of 121 companies. Based on data availability, the type of data used is secondary data in the form of financial statements of manufacturing sector companies listed on the Indonesia Stock Exchange in the period 2013 - 2017.